2017
DOI: 10.1038/s41598-017-07088-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental estimation and analysis of variance of the measured loss power of magnetic nanoparticles

Abstract: Magnetic nanoparticles dissipate heat when exposed to alternating magnetic fields (AMFs), making them suitable for cancer hyperthermia. Therapeutic heating applications demand accurate characterization of the heating power dissipated by the particles. Specific loss power (SLP) generated by magnetic nanoparticles is estimated from calorimetric heating measurements. Such measurements require adiabatic conditions, yet they are typically performed in an AMF device with non-adiabatic conditions. We have measured he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 52 publications
2
99
0
Order By: Relevance
“…This study [59] also compared heating properties of nanoparticles within an aqueous environment, inside cells, and within tumors, and showed that MNPs lose heating power when internalized by cells. Despite similarities to ILP and SAR values from the literature, the experimental set-ups for heating measurements can have potential sources of error [18,60,61], with sample volume being one of them. In a few studies [18,60] it was shown that decreasing sample volumes results in lower SAR values.…”
Section: Sar Values and Calculation Methods (Ism Csm And Blm)mentioning
confidence: 99%
See 3 more Smart Citations
“…This study [59] also compared heating properties of nanoparticles within an aqueous environment, inside cells, and within tumors, and showed that MNPs lose heating power when internalized by cells. Despite similarities to ILP and SAR values from the literature, the experimental set-ups for heating measurements can have potential sources of error [18,60,61], with sample volume being one of them. In a few studies [18,60] it was shown that decreasing sample volumes results in lower SAR values.…”
Section: Sar Values and Calculation Methods (Ism Csm And Blm)mentioning
confidence: 99%
“…The first two methods, ISM and CSM, are linear approximations of the phenomenological BLM and can be used in certain situations. ISM would be accurate for adiabatic measurements with no chemical or physical changes within the samples [61].…”
Section: Sar Values and Calculation Methods (Ism Csm And Blm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, another important factor to be considered when applying a novel formulation for MH is the overall concentration of the respective NPs at the tumor site [50,51]. Specifically, NPs with a low specific loss power (SLP) need to be more concentrated in the tumor, with the consequent disadvantages of bioaccumulation and long-term toxicity [52,53].…”
Section: Figurementioning
confidence: 99%